Corporate Governance and The Modification of Audit Opinion: A Study in The Jordanian Market (International Journal of Applied Research in Management and Economics, 2020)
The objective of this study is to examine the relationship between some Corporate Governance indicators and the probability of modifying the independent auditor opinion in the Jordanian market. The sample consists of 104 non-financial firms listed on Amman stock Exchange for the year 2015. The logistic regression via SPSS is used to analyze the data. The results show that firm’s profitability (measured by ROA) and the number of institutional investors on the board of directors are significant negative predictors of the probability of receiving modified audit opinion by the firm. That is the higher the firm’s ROA and the larger number institutional investor representatives on the board of directors the less likely the firm will receive a modified audit opinion. On the other hand, the results also show that the board of directors’ size is significant positive predictor of receiving a modified audit opinion by the firm. That is the larger the size of the board of directors the more likely the firm will receive a modified audit opinion. Although, it is an unexpected result it agrees with some other studies results. Finally, board independence, board activity and the presence of audit committee have no significant impact on the type of audit opinion the firm receives.